"How Do You Work Out This Zoom Classroom?": Pre-service English Teachers Challenges and Expectations During Transition to Online Teaching Practicum - Gin Gin Gustine (Research And Innovation In Language Learning (RILL), 2021)
The role of teaching practicum for pre-service teachers in significant and an integral part in many teacher education programs. Against this backdrop, the challenges and expectations from pre-service English teachers during the online teaching practicum, as the result of Covid-19 physical and social distancing, have not been explored well. This qualitative case study research is expected to shed lights on the expectations and challenges faced by pre-service English teachers who conducted their teaching practicum online during the Covid-19 pandemic. Data were generated from individual and focus group interview with nine pre-service English teachers who were all conducting their online teaching practicum period from February-July 2020. Result showed that the challenges pre-service English teachers faced were lack of pedagogical knowledge in how to teach in online class environment and lack of knowledge in online assessment. To solve these problems, pre-service teachers expect a strong support and assistance from both school teachers and university supervisors in terms of improving their knowledge and skills in using appropriate Information Communication Technology in the class.